MODIFIED NANOPARTICLES WITH ANTIBACTERIAL PROPERTIES INVOLVED IN ORAL PATHOLOGY - Dragoș Ioan Virvescu; Zinovia Surlari; Dana Gabriela Budală; Dragoș Nicolae Frățilă; Mihaela Scurtu; Ionut Alexandru Luchian (Romanian Dental Association for Education, 2022)
Introduction. As the area of nano-based platforms for antimicrobial treatment aimed at pathogenic oral biofilms continues to expand, this review serves to bring together researchers from several disciplines to foster more collaboration and discovery among dental practitioners.